Cleaner utilization of electroplating sludge by bioleaching with a moderately thermophilic consortium: A pilot study. (October 2019) - Zhou, Wenbo; Zhang, Lijuan; Peng, Jing; Ge, Yang; Tian, Zhuang; Sun, Jianxing; Cheng, Haina; Zhou, Hongbo
Abstract: The semi-pilot scale bioleaching of electroplating sludge by the moderately thermophilic acidophilic consortium was carried out for the first time. During the microbial cultivation, Leptospirillum ferriphilum CS13, Acidithiobacillus caldus S2, and Sulfobacillus acidophilus CS5 could grow rapidly in a 300 L aeration packed reactor, in which the total suspended cell concentration could fluctuate around 3 × 10 8  cells/mL and the community structure remained relatively stable. During the bioleaching process, the microbial stock solution could effectively leach heavy metals from electroplating sludge in a stirred reactor within a few hours. Meanwhile, the effects of pH, temperature, the quantity of active culture, and liquid-solid ratio on the bioleaching behavior were also investigated. The optimal conditions for electroplating sludge bioleaching were pH 1.5, temperature 45 °C, bacterial liquid ratio 40%, liquid-solid ratio 4:1 L kg −1, and leaching time 5 h. The total removal rate of various heavy metals in electroplating sludge was over 99%. The bioleaching residue was successfully passed the TCLP test, and the total contents of heavy metals in the residue were also well below the regulatory criteria. In addition, the XRD analysis of the bioleaching residue was also confirmed that the moderately thermophilic consortium bioleaching provided a cleaner process than chemical leaching on the removal of the residual fraction metals, which was feasible and attractive for industrial treatment of electroplating sludge. Graphical abstract: Image 1 Highlights: Detoxification of electroplating sludge was realized through bioleaching in a pilot scale. The pH, temperature, cell density and liquid-solid ratio directly affected bioleaching rate. Separating microbial cultivation from bioleaching could shorten the total treatment time. The biological detoxification process has some advantages over simple ferric leaching. The detoxification degree was verified through total mass, XRD, BCR and TCLP analysis.